Diffusion tensor imaging and voxel based morphometry study in early progressive supranuclear palsy. Issue 4 (23rd November 2005) - Padovani, A; Borroni, B; Brambati, S M; Agosti, C; Broli, M; Alonso, R; Scifo, P; Bellelli, G; Alberici, A; Gasparotti, R; Perani, D
Abstract : Background: A comprehensive characterisation of grey and white matter changes in progressive supranuclear palsy (PSP), the second most common extrapyramidal syndrome after Parkinson disease, is still not available. Objective: To evaluate grey and white matter changes in mild PSP patients by voxel based morphometry (VBM) and diffusion tensor imaging (DTI), respectively. Methods: 14 mild PSP patients and 14 healthy controls entered the study and underwent a clinical and neuropsychological evaluation according with a standardised assessment. Each subject had a structural magnetic resonance imaging (MRI) study. Processing analysis of MRI data was carried out according to optimised VBM and fractional anisotropy was determined. Results: Compared with the controls, in PSP patients VBM analysis showed a significant clusters of reduced grey matter in premotor cortex, frontal operculum, anterior insula, hippocampus, and parahippocampal gyrus, bilaterally. With regard to subcortical brain regions, the pulvinar, dorsomedial and anterior nuclei of the thalamus, and superior and inferior culliculum were affected bilaterally. A bilateral decrease in fractional anisotropy in superior longitudinal fasciculus, anterior part of corpus callosum, arcuate fascicolus, posterior thalamic radiations, and internal capsule, probably involving the cortico-bulbar tracts, was present in PSP patients. Conclusions: These data provide evidence for both grey and white matter degeneration in PSP from the early disease stage. These structural changes suggest that atrophy of cortical and subcortical structures and neurodegeneration of specific fibre tracts contribute to neurological deficits in PSP.